Is Socioeconomic Advantage Associated With Positive Health Behaviors and Health Outcomes Among Asian Indians?. (28th February 2019) - Gor, Beverly; Nepal, Vishnu P.; Dongardive, Rashmi; Dorai, V. K.; Pande, Mala
Objective: The South Asian Health Needs Assessment was conducted to collect health status information on the rapidly growing Asian Indian (AI) community in the Houston area. Many were highly educated and reported high income levels, factors usually associated with better health outcomes. This study examined the relationship between socioeconomic advantage and the health behaviors and health outcomes of AIs. Methods: We analyzed cross-sectional survey data from a convenience sample of 1416 AIs. Income was categorized as low, medium, and high. Descriptive statistics were generated by income categories and weighted multinomial regression analyses were conducted to examine the association of income with health behaviors and outcomes, adjusting for age, sex, health insurance, and years in the United States. Results: Income was positively associated with better self-rated health, higher body mass index, moderate physical activity, having shingles vaccine, and cervical cancer screening. Income was inversely associated with perceived stress and heart disease. However, income was not significantly associated with alternative therapies, cigarette smoking, alcohol consumption, self-reported overweight/obesity, fruit and vegetable consumption, diabetes, high blood pressure, high cholesterol and screening for breast, prostate, and colon cancer. Conclusions: Socioeconomic advantage was not consistently associated with positive health outcomes or desired health behaviors among AIs. We speculate that other factors, including cultural beliefs and acculturation may also impact health behaviors and health outcomes in this group. Further studies examining the influence of these variables on health behaviors and health outcomes are warranted.